2015
DOI: 10.1093/nar/gkv1381
|View full text |Cite
|
Sign up to set email alerts
|

Circularization pathway of a bacterial group II intron

Abstract: Group II introns are large RNA enzymes that can excise as lariats, circles or in a linear form through branching, circularization or hydrolysis, respectively. Branching is by far the main and most studied splicing pathway while circularization was mostly overlooked. We previously showed that removal of the branch point A residue from Ll.LtrB, the group II intron from Lactococcus lactis, exclusively leads to circularization. However, the majority of the released intron circles harbored an additional C residue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…During the formation of circRNAs either 2 0 -5 0 or 3 0 -5 0 linkages have been detected. 8,9 The resulting molecular "rings" or RNA circles resist degradation by exoribonucleases that require free termini and/or may have increased melting point in comparison to linear nucleic acid molecules. Circularization of RNA molecules may thus drastically influence the structure and/or shape of these molecules, presumably reflecting structural constraints brought about by circularization.…”
Section: Introductionmentioning
confidence: 99%
“…During the formation of circRNAs either 2 0 -5 0 or 3 0 -5 0 linkages have been detected. 8,9 The resulting molecular "rings" or RNA circles resist degradation by exoribonucleases that require free termini and/or may have increased melting point in comparison to linear nucleic acid molecules. Circularization of RNA molecules may thus drastically influence the structure and/or shape of these molecules, presumably reflecting structural constraints brought about by circularization.…”
Section: Introductionmentioning
confidence: 99%
“…To study the splicing pathway leading to the incorporation of additional nucleotides at the splice junction of group II intron circles [ 17 ] we performed an RT-PCR reaction across the Ll.LtrB-ΔLtrA+LtrA lariat and circle splice junctions ( Fig 2 ) [ 17 , 18 ]. We cloned and sequenced the amplicons located in the faint smear above the RT-PCR band that corresponds to perfect lariat and circle splice junctions ( Fig 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…We recently unveiled and characterized at the molecular level the circularization pathway of Ll.LtrB, the model group II intron, from the gram-positive bacterium Lactococcus lactis [ 17 , 18 ]. Our work showed that the intron excises simultaneously through the branching and circularization pathways in vivo leading to the accumulation of both intron lariats and circles respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether Ef.PcfG is functional in its native environment, we first assessed its ability to splice in vivo by looking for both released intron and ligated exons by RT-PCR on E. faecalis (SF24397ΔpEF1071) total RNA extracts (Fig. 2a ) [ 35 , 36 ]. Sequencing of the major amplicons for both ligated exons and released intron showed that they correspond respectively to accurately joined pcfG exons (1587 bp) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the splicing efficiency of our various intron constructs, we performed poisoned primer extension assays (Fig. 4a ) [ 35 , 39 ]. This assay compares the ratio of ligated exons to precursor mRNA from total RNA extracts.…”
Section: Resultsmentioning
confidence: 99%